Making the world in our image: the New York Times & Financial Times' mediation of China's public diplomacy messages - Hong, Tony (2019)
My thesis argues that a major condition for the success of China’s public diplomacy stems from the support or opposition of the targeted country’s news media. Using content analysis and adapting Fairclough’s discourse analytical approach, this thesis analyses the ideas and discourses associated with China in two major influential news organisations: The Financial Times and the New York Times. Drawing on David Vukovich’s writings on Sinological-Orientalism and Chengxin Pan’s Bifocal Lens of Threat and Opportunity to analyse news texts and other supplementary sources such as semistructured interviews with China correspondents, the thesis provides insights and detailed analysis of the mechanisms involved in the production of China’s representation in the news. The project provides a fresh perspective on how China’s strategic narratives that are promoted by its public diplomacy face a difficult news media environment because of its antagonism towards authoritarian governments.